Discussion on the Key Problem of RV Reducer Localization Batch Production - Xu Honghai; Xie Xiongwei; Guan Tong (Jixie chuandong)
On the consideration of the development trend of industrial robots and domestic market situation& research status of RV reducer,the difficult problems need to be solved in the domestic batch manufacturing of RV reducer are put forward,such as national standards for design,manufacture and inspection,machining equipment for special part,wear and lubrication and intelligent inspection and assembly. The relevant solutions are discussed and the strategic thinking and suggestion are provided for RV reducer technology and industry of robot field in China.